Steering Tertiary Education : Toward Resilient Systems that Deliver for All - Arnhold, Nina (World Bank, Washington, DC, 2021)
As the world seeks to build back better into a new era of green and equitable economic growth, tertiary education systems are at the heart of the big transformations required throughout economies and societies. Tertiary education is vital for the development of human capital and innovation. Strategic and effective investments in tertiary education can serve every country - from the poorest to the richest - by developing its talent and leadership pool, generating, and applying knowledge to local and global challenges, and participating in the global knowledge economy. Effective tertiary education sectors ensure that countries have well-trained doctors, nurses, teachers, managers, engineers, and technicians who are the main actors of effective education and health service delivery and public and private sector development. Decades of insufficient and ineffective investment in postsecondary education and the advanced skills developed through higher learning opportunities have only exacerbated global equity gaps. This paper describes the approach of the World Bank to support the development of effective, equitable, efficient, and resilient tertiary education systems and institutions. It discusses and illustrates five principles that guide the Bank's financial and policy advisory support to STEER tertiary education systems toward optimizing their contribution to equitable and green growth: (i) building diversified Systems, (ii) investing smartly in new Technologies, (iii) ensuring Equity in access and financing, (iv) achieving Efficiency in resource utilization, and (v) acquiring Resilience in service delivery so that learning continues.